Solving by elimination method.
We have the following system of equations:
![\begin{gathered} -6x-y=13 \\ 9x-4y=19 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ek8647dm0un94okylmgk777dmzfblkdbdz.png)
we can multiply the first equation by -4, then we have the equivalent system:
![\begin{gathered} 24x+4y=-52 \\ 9x-4y=19 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pysr9oj01f4wn7o9h226ykruomsxg2613n.png)
If we add both equations, we obtain
![\begin{gathered} 24x+9x=-52+19 \\ 33x=-33 \\ x=(-33)/(33) \\ x=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rtnpnbkjzua33nsr5qfjy31ck525ug607x.png)
now, we can substitute this values into the first original equation, It yields
![\begin{gathered} -6(-1)-y=13 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/l3hpiqsxfms051rysvqk6ryp1ius5t373y.png)
then, we have
![\begin{gathered} 6-y=13 \\ -y=13-6 \\ -y=7 \\ y=-7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o7ot4gf764g6cb0tfjnmm9pdv3bdnxzatp.png)
Therefore, the answer is x= -1 and y= -7, which correspond to the point (-1,-7).